Knowledge Management Dalam Pemilihan Teknologi Administrasi P3M Politeknik Negeri Cilacap - Cahya Vikasari (P3M Politeknik Negeri Cilacap, 2020)
Application of technology is expected to simplify administrative work management. Cilacap State Polytechnic has P3M unit in charge of managing research and community service conducted by lecturers. Intellectual capital in P3M units that are easily lost, internal communication problems in P3M units that can inhibit knowledge and work sharing and the occurrence of errors’ duplication in P3M archive activities are some obstacles that occur during data management process. The technology application in the concept of knowledge management by considering the number of participants and the duration of the conversation is needed, therefore it can be concluded that the technology which can be used is presentation, computer share, chat, email, application. Applications made are suited to the needs of the data management application in the P3M unit. Successful application of technology can use the concept of ACKM and is applied in tertiary institutions.